Deciphering the Differences Between Epstein–Barr Virus‐Associated and Negative Gastric Cancer in the Prospect of CDKN2A Genomic Alterations and Lymphoid Infiltration - Fuda Xie; Bonan Chen; Yang Lyu; Peiyao Yu; Canbin Fang; Kam Tong Leung; Shouyu Wang; Dazhi Xu; Jun Yu; Kwok Wai Lo; Ka Fai To; Wei Kang (Cancer Medicine)
ABSTRACT Background Gastric cancer (GC) is a major health concern worldwide. One important contributing factor is the presence of the Epstein‐Barr virus (EBV). However, the molecular pattern of how EBV participates in the malignant transition process remains unclear. Methods GC samples were stained by immunohistochemistry, fluorescent and EBV‐encoded small RNA in situ hybridization to identify CD8 expression, CDKN2A genomic alteration, and EBV existence. Functional potentials of EBV infection were predicted by bioinformatic enrichment analysis. Results CDKN2A genestayed intact in all EBV‐associated GC cases. Meanwhile, CDKN2A deletion (8.43% cases) was exclusive to EBV‐negative GC cases. Furthermore, EBV infection was positively correlated with CD8+T cell infiltration, and both of them predicted better prognosis. Conclusion This study highlighted the comprehensive impact of EBV infection in GC formation and proposed a thought‐provoking observation for further investigation into the roles of CDKN2A and EBV infection in gastric tumorigenesis.